Pharmacological inhibition of myostatin improves skeletal muscle mass and function in a mouse model of stroke. Issue 1 (December 2017) - Desgeorges, Marine Maud; Devillard, Xavier; Toutain, Jérome; Castells, Josiane; Divoux, Didier; Arnould, David Frédéric; Haqq, Christopher; Bernaudin, Myriam; Durieux, Anne-Cécile; Touzani, Omar; Freyssenet, Damien
Abstract In stroke patients, loss of skeletal muscle mass leads to prolonged weakness and less efficient rehabilitation. We previously showed that expression of myostatin, a master negative regulator of skeletal muscle mass, was strongly increased in skeletal muscle in a mouse model of stroke. We therefore tested the hypothesis that myostatin inhibition would improve recovery of skeletal muscle mass and function after cerebral ischemia. Cerebral ischemia (45 minutes) was induced by intraluminal right middle cerebral artery occlusion (MCAO). Swiss male mice were randomly assigned to Sham-operated mice (n = 10), MCAO mice receiving the vehicle (n = 15) and MCAO mice receiving an anti-myostatin PINTA745 (n = 12; subcutaneous injection of 7.5 mg.kg−1 PINTA745 immediately after surgery, 3, 7 and 10 days after MCAO). PINTA745 reduced body weight loss and improved body weight recovery after cerebral ischemia, as well as muscle strength and motor function. PINTA745 also increased muscle weight recovery 15 days after cerebral ischemia. Mechanistically, the better recovery of skeletal muscle mass in PINTA745-MCAO mice involved an increased expression of genes encoding myofibrillar proteins. Therefore, an anti-myostatin strategy can improve skeletal muscle recovery after cerebral ischemia and may thus represent an interesting strategy to combat skeletal muscle loss and weakness in stroke patients.